Remission from Chronic Anorexia Nervosa With Ketogenic Diet and Ketamine: Case Report - Scolnick, Barbara; Zupec-Kania, Beth; Calabrese, Lori; Aoki, Chiye; Hildebrandt, Thomas (Frontiers in Psychiatry, 2020)
Background. Severe enduring anorexia nervosa is a tragic disease with no known effective pharmacological or behavioral treatment. We report the case of a 29 year-old woman who struggled with severe and enduring anorexia nervosa for 15 years, and experienced a complete recovery following a novel treatment of adopting a ketogenic diet followed by ketamine infusions. Her remission has persisted for over 5 months. Case Presentation. At age 14.5, the patient embarked on an effort to “eat healthy.” She quickly lost control of the dieting, developed associated compulsions and obsessions about food, body dissatisfaction, emotional lability and lost 30 pounds. She was hospitalized for 6 weeks, and while she regained some weight, she did not attain full weight restoration. For 15 years, she continued to eat in a restrictive manner, exercise compulsively, and have intermittent periods of alcohol dependence. Nevertheless, she always hoped to get well, and at age 29, she agreed to try a novel treatment for anorexia nervosa. Conclusions This treatment was derived largely from work on the rodent activity-based-anorexia model. Other sources of inspiration for this treatment were the proven effectiveness of the ketogenic diet for other central nervous system disorders especially seizures; and the emergence of ketamine infusion as a treatment for depression. This is the first report of a ketogenic diet for anorexia nervosa. There is one very encouraging study of ketamine for anorexia nervosa, published in 1998. It is likely these modalities are synergistic. While this is only one case, it gives hope that a treatment for chronic anorexia nervosa may be in sight.